Macro-anatomical investigations on the skeletons of hedgehog (Erinaceus europaeus L.). II. ossa membri pelvini - Özkan, Zait Ender (My University, 2002)
In this study, three adult male hedgehogs (Erinaceus europaeus Linnaeus) were used to investigate the bones of hind limb. The spina iliaca ventralis caudalis was absent. The symphysis pelvis was formed by symphysis pubis and it was an interpubic ligamentous tissue in hedgehogs. The average Vialleton angle was measured as (8°). Average distance between the midacetabulum and tuber coxae was 39.2 mm and average distance between the midacetabulum and ischial tuberosity (tuber ischiadicum) was 13.8 mm. There were three trochanters on the femur. The tibia and fibula were fused almost in the distal half. There were 7 tarsal bones and the pedis was complete with five digits.
Keywords: Erinaceus europaeus L.; Hedgehog; Ossa membri pelvini